Analisis Faktor Pemungkin Terhadap Rendahnya Pemanfaatan Pelayanan Poli Gigi - Heni Lestari; Lolita Sary; Andoko Andoko (MAHESA : Malahayati Health Student Journal, 2021)
ABSTRACT : ANALYSIS OF IMPORTANT FACTORS ON THE LOW UTILIZATION OF DENTAL POLICE SERVICES AT PUSKESMAS REBANG TANGKAS WAY KANAN Introduction: Dental polyclinic service is one of the types of services in a public health center that provides dental and oral health services in the form of dental and oral health checks, medication and provision of basic dental and oral health medical measures. The results of the pre-survey in the working area of Puskemas Rebang Tangkas, Way Kanan Regency towards 10 respondents, 7 of whom prefer to seek treatment at a dentist or a dental clinic. Meanwhile, 3 of them continued to carry out dental examinations at the health center, with consideration of cheaper payments. Purpose: Therefore, this study aims to determine the enabling factors associated with the use of dental clinic at the Rebang Tangkas Community Health Center, Way Kanan Regency in 2020.Method: This type of research used in this research is quantitative. The research design used in this study was cross sectional. The population in this study were all 118 people in the work area of Puskesmas Rabang Tangkas, Way Kanan Regency. Sampling using purposive sampling.Results: Based on the results of data collection, it is known that the use of dental polyclinic services to respondents in the work area of the Rebang Tangkas Community Health Center, Way Kanan Regency in 2020 with categories that utilize dental polyclinic services as many as 44 respondents (37.3%) and those who do not utilize dental poly services are 74 respondents (62.7%). Based on the results of statistical tests, it was obtained p value 0.014, and 0.038 and or p value <0.05, which means that there is a relationship between facilities and infrastructure factors and the low utilization of dental health services at Puskesmas Rebang Tangkas Way Kanan Regency in 2020.Conclusion: There is a relationship between health facilities and infrastructure and the low utilization of dental poly services at Puskesmas Rebang Tangkas, Way Kanan district. Suggestions from researchers that good service will be obtained if facilities and infrastructure that meet the standards are available in health facilities. This is closely related to procurement management where attention is needed and good implementation of the planning of the facilities and infrastructure required.  Keywords: Facilities, Health Infrastructure, Dental Clinic    INTISARI: ANALISIS FAKTOR PEMUNGKIN TERHADAP RENDAHNYA PEMANFAATAN PELAYANAN POLI GIGI DI PUSKESMAS REBANG TANGKAS KABUPATEN WAY KANAN  Pendahuluan: Pelayanan poli gigi merupakan salah satu dari jenis layanan di puskesmas yang memberikan pelayanan kesehatan gigi dan mulut berupa pemeriksaan kesehatan gigi dan mulut, pengobatan dan pemberian tindakan medis dasar kesehatan gigi dan mulut. Hasil prasurvey diwilayah kerja Puskemas Rebang Tangkas Kabupaten Way Kanan terhadap 10 orang responden, 7 diantaranya lebih memilih berobat kedokter gigi, atau klinik gigi. Sedangkan 3 diantaranya tetap melakukan pemeriksaan gigi di puskesmas, dengan pertimbangan pembayaran yang lebih murah. Tujuan : Penelitian ini bertujuan untuk mengetahui faktor pemungkin yang berhubungan dengan  pemanfaatan poli gigi di Puskesmas Rebang Tangkas Kabupaten Way Kanan Tahun 2020.Metode : Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif. Rancangan penelitian yang digunakan dalam penelitian ini adalah cross sectional. Populasi dalam penelitian ini adalah seluruh masyarakat yang ada di wilayah kerja Puskesmas Rabang Tangkas Kabupaten Way Kanan sebanyak 118 orang.  Pengambilan sampel menggunakan Purporsive Sampling.Hasil : Berdasarkan hasil dari pengumpulan data diketahui bahwa pemanfaatan pelayanan poli gigi pada responden di wilayah kerja Puskesmas Rebang Tangkas Kabupaten Way Kanan Tahun 2020 dengan kategori yang memanfaatkan pelayanan poli gigi sebanyak 44 responden (37,3%)  dan yang tidak memanfaatkan pelayanan poli gigi sebanyak 74 responden (62,7%). Berdasarkan hasil uji statistik, didapatkan p value 0,014, dan 0,038 dan atau p value < 0,05 yang artinya terdapat hubungan antara faktor sarana dan prasarana dengan rendahnta pemanfaatan pelayanan kesehatan poli gigi di Puskesmas Rebang Tangkas Kabupaten Way Kanan Tahun 2020.Kesimpulan : Ada hubungan antara sarana dan prasarana kesehatan dengan rendahnya pemanfaatan pelayanan poli gigi di Puskesmas Rebang Tangkas Kabupaten Way Kanan. Saran dari peneliti bahwa pelayanan yang baik akan didapatkan jika sarana dan prasarana  yang memenuhi standar tersedia di fasilitas kesehatan. Hal ini berkaitan erat dengan manajamen pengadaan di mana perlunya perhatian dan implementasi yang baik dari perencanaan sarana dan prasarana yang dibutuhkan.  Kata Kunci     : Sarana, Prasarana Kesehatan, Poli Gigi